Look Behind Me! Highly Informative Picture Backgrounds Increase Stated Generosity Through Perceived Tangibility, Impact, and Warm Glow - Caserotti, Marta; Vacondio, Martina; Maze, Maya; Priolo, Giulia (Frontiers in Psychology, 2022)
In this study we investigated whether background information of a visual charity appeal can influence people’s motivation to donate and hypothetical amount donated. Specifically, participants were presented with a charity appeal to help a local hospital respond to the COVID-19 emergency depicting a man sitting on a bed in a hospital room. The amount of visual details (i.e., medical equipment) depicted in the background was manipulated according to three conditions: 1) “high information” condition (i.e., room full of medical equipment), 2) “low information” condition (i.e., room with few medical equipment), and 3) “no information” condition (i.e., non-contextual background). We investigated whether the amount of visual background details would have increased tangibility of the cause measured as hospital’s adequate preparedness to deal with the COVID-19 emergency and severity of the patient’s medical conditions. We also investigated whether increased tangibility, elicited by a higher amount of background information, would heightened participants’ perceived impact of their donation and warm glow, which in turn would have led to increased motivation to donate and the amount donated. We found no significant direct effect of condition on the donated amount. However, Path models revealed that more background information positively influenced participants’ motivation to donate and amount donated indirectly through increased tangibility, impact, and warm glow. Finally, we showed that higher risk perception of COVID-19 was associated with higher donations. Results are discussed in line with relevant literature.